2014
DOI: 10.15578/squalen.v9i1.91
|View full text |Cite
|
Sign up to set email alerts
|

PURIFICATION AND CHARACTERIZATION OF THE NEWLY THERMOSTABLE PROTEASE PRODUCED BY Brevibacillus thermoruber LII ISOLATED FROM PADANG CERMIN HOTSPRING, INDONESIA

Abstract: Thermostability is among of the vital enzyme characteristics for industrial application. Brevibacillus thermoruber LII was obtained as a potential isolate from the previous research which screened the potential thermostable protease producing bacteria from Indonesian hotspring. The newly thermostable protease produced by thermophilic Brevibacillus thermoruber LII had been purified and characterized. It was predicted that the pure enzyme obtained from Brevibacillus thermoruber LII was homo hexameric, having mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…Monomeric proteases with molecular weights between 60 and 66 kDa from Brevibacillus sp. have been reported in literature [ 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Monomeric proteases with molecular weights between 60 and 66 kDa from Brevibacillus sp. have been reported in literature [ 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Weak activities were still observed at pH 5.0 and 11.0. The majority of extracellular proteases reported in literature from Brevibacillus members were alkaline proteases with optimal pH around 8.0 [ 46 , 47 , 50 , 51 ], and acid proteases were rarely reported [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentrated enzyme precipitate was separated by centrifugation (EDLAB Clinical, Indonesia) at 15,000 rpm for 10 mins. (Zilda et al, 2014) . The precipitate obtained was then dialyzed by placing it in a cellophane bag, then soaking it in 0.05 and 0.025 M phosphate bu ers at pH 7 and stirring using a stirrer at 4°C for one night.…”
Section: Partial Puri Cation Of Bacterial Proteasementioning
confidence: 99%
“…Microbial transglutaminase is not influenced by Ca 2+ , so the presence of metal chelating compounds such as EDTA could not inhibit enzyme activity (Lin et al, 2008). The activity of the purified transglutaminase was inhibited partially by PMSF indicating that active site contained serin (Susanti, 2003;Zilda, 2013). Tsai et al (1996) reported that transglutaminase produced by Streptoverticillium ladakanum is strongly inhibited by PMSF but not affected by EDTA.…”
Section: Effect Of Different Metal Ions and Inhibitorsmentioning
confidence: 99%